Effect of pH in Metal Salts Ability Study Towards Anionic Surfactant Detection - Siti Munirah Binti Zainudin,; Hashim, Nor Haslina (Progress in Engineering Application and Technology, 2023)
Extensive used of surfactants mainly anionic surfactant (AS) in cleaning products such as detergent, soap and shampoo greatly affect the water quality when released in the environment. A simple and rapid spectrophotometric method in detecting AS in water is aimed to replace the current conventional methylene blue active substance (MBAS) method, which is tedious, time-consuming and requires high amount of toxic solvent. In this study, Copper (II) bromide metal salts was chosen among Nickel (II) Acetate Tetrahydrate, Copper (II) Acetate and Copper (II) Chloride because of its colour, solubility in water, stability and good performance compared to other shortlisted metal salts. The interaction between selected Copper (II) bromide metal salts, SDS and TEA with the influence of pH is used as the method to obtain absorbance value at 650 nm wavelength and to construct the calibration curve. The R-squared of 0.9921 was obtained from linearity graph of absorbance against concentration together with the linear equation, y = 0.0812x + 0.05 that was used to find the final concentration for adjusted pH 3.3 to pH 8 in different concentration of SDS from the constructed calibration curve. Experiment has demonstrated that Copper (II) bromide surfactant responses were slightly varied in various concentration of solution’s pH. UV absorption were found to be in negative and positive values with the change of pH of the solutions. In this study, the positive values of UV adsorption implied the suitability of working pH at 5.6 to 6.8 for Copper (II) bromide and surfactant response. Further investigation need to be conducted in order to confirm the validity of the method conducted and findings obtained in this study.